The intercultural transfer of football: the contexts of Germany and Argentina. Issue 10 (3rd October 2017) - Adam, Thomas
Abstract: Historians of sport have paid little attention to the ways in which modern sports such as football were transferred from its place of origin to receiving cultures around the globe. While it is recognized that this ball game emerged in nineteenth-century English public schools, little is known about the transformations this game underwent in becoming modern-day German football and modern-day Argentine football. Applying the model of intercultural transfer, my contribution will investigate the process of the transfer of this ball game from English public schools to German and Argentine high schools. The emergence of football and its transfer across the world was carried out by teachers and students and it was part of educational reform since this game offered an alternative to the traditional ways of imposing discipline. Discipline did not come from an outside force such as the teacher but from the rules of the game. This game, further, encouraged team work in order to achieve victory and offered sons of middle-class families an introduction into the mechanisms of the capitalist market. The introduction of soccer into urbanizing cultures was also part of social hygiene debates and many of the protagonists of this game were also involved in social reform debates about improving the quality of living in modern cities.